Improving The Speed And Technique of Breaststroke Swimming by Development The Strength Power of A Swimmer - Valijonov Hamid Olimjonovich (Web of Journals Publishing, 2023)
The article deals with the purpose of improving the efficiency of breaststroke swimming technique by developing the strength of boy’s swimmers 12-14 years old.
Keywords: Breaststroke swimming, Training, Improvement, Speed, Explosive power, Strength.